قراءة في ديوان (من أوراق الحلاج الآخر) للشاعرة المغربية أمينة المريني: الارتحال بين رحيق العشق الإلهي ورحيق العشق المكاني: Journeying Between the Nectar of Divine Love and The Nectar of Spatial Love: A Reading of the Collection (From The Papers of the Other Hallaj) By The Moroccan Poet Amina Al-Marini - Ghazioui, Mohamed (SIBAWAYH Arabic Language and Education, 2024)
تعد أمينة المريني من الشاعرات المقتدرات اللواتي وضعن بصمتهن ليس في الشعر المغربي الحداثي فحسب، بل في الشعر العربي المعاصر، إنها الشاعرة التي سحرت القراء بقصائدها الماتعة، وتجربتها المختمرة، وتكوينها العلمي الرصين المفصوح عنه في منجزاتها الشعرية الثرة من خلال دواوينها. ومن هاته الدواوين ديوان(من أوراق الحلاج الآخر) الذي ضم بين دفتيه ثلاث قصائد (كأس، وعبودية، ومفازات)، كلها عشق واشتياق واحتراق، كلها سبر في أغوار الطفولة وسرد لأحلامها ولحظاتها الماتعة المحفورة في الذاكرة. إن عزف الشاعرة على عنصر المكان فتق شاعريتها، وجعلها تبحر في طفولتها، وفي قطار حياتها، وهي تتنقل من مكان إلى مكان، وتقتنص من رحيق كل الأمكنة ما يجعل بمكنتها تقديم منجز شعري كله تعبير عن أشعار ماتعة.تهدينا فاطمة المريني من خلال ديوانها المدروس رؤية شعرية في منتهى الاقتدار، رؤيا تكشف عن اختمار لشعرية أنثوية حداثية تنم عن ذائقة شعرية مائزة. وبالرغم أن الشاعرة أسست لتجربتها من خلال مقومات البناء الحداثي للشعر المعاصر شكلا ومضمونا، فإن تجربتها لها فرادتها من خلال توظيفها لمقومات فنية وأسلوبية قلما نجدها لدى شاعرات حداثيات أُخريات. وقد رمنا من خلال دراستنا هاته تسليط الضوء على هذا المنجز المتميز واستكناه بعض خفاياه، وسبر أغوار هاته التجربة الشعرية التي جعلت المكان منطلق عشقها، ومن شخصية الحلاج ملهمة لها، والشاعرة في ذلك تنتقل من رحيق العشق الإلهي إلى رحيق العشق المكاني لتتحفنا بإبداع شعري في منتهى الجمالية يستحق أكثر من دراسة.Amina Al-Marini is considered one of the capable poets who made her mark not only in modern Moroccan poetry, but also in contemporary Arab poetry. She is the poet who enchanted readers with her delightful poems, her fertile experience, and her sober scientific composition expressed in her rich poetic achievements through her collections. Among these collections is a collection of poems (From the Papers of the Other Hallaj), which included three poems (A Cup, Bondage, and Rewards), all of them love, longing, and burning, all of them exploring the depths of childhood and recounting its dreams and joyful moments engraved in memory. The poet’s playing on the element of place broke her poetry and made her navigate her childhood and the train of her life, as she moves from place to place and seizes the nectar of all places, which makes her able to present a poetic achievement that is all an expression of pleasant poems. Fatima Al-Marini, through her study book, guides us with an extremely powerful poetic vision, a vision that reveals the fermentation of modern feminine poetry that expresses a distinct poetic taste. Although the poet established her experience through the elements of the modernist construction of contemporary poetry in form and content, her experience has its uniqueness through its use of artistic and stylistic elements that we rarely find with other modernist poets. Through our study, we aimed to shed light on this outstanding achievement and grasped some of its secrets, and to explore the depths of this poetic experience that made the place the source of her love, and from the personality of Al-Hallaj as an inspiration for her. The aesthetic is worth more than studying.Keywords: Sufi poetry, spatial love, divine love, poetic vision, poetic creativity, exit, poetic spring